2001
DOI: 10.1182/blood.v98.10.3006
|View full text |Cite
|
Sign up to set email alerts
|

Prostratin: activation of latent HIV-1 expression suggests a potential inductive adjuvant therapy for HAART

Abstract: Prostratin is a unique phorbol ester that stimulates protein kinase C activity but is nontumor promoting. Remarkably, prostratin is also able to inhibit de novo human immunodeficiency virus type 1 (HIV-1) infection yet up-regulate viral expression from latent proviruses. Prostratin's lack of tumor promotion, coupled with its ability to block viral spread yet induce latent proviral expression, prompted studies to determine whether this compound could serve as an inductive adjuvant therapy for patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
301
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(321 citation statements)
references
References 32 publications
19
301
1
Order By: Relevance
“…We find that prostratin effectively activates the latent provirus in multiple independently derived J-Lat T-cell clones. These results are in agreement with recently published results demonstrating prostratin-mediated activation of latent virus in the SCID-HU Thy/Liv system and in the blood of patients with HAART-suppressed HIV (14,15). We observed that prostratin induces similar levels of proviral gene transcription as TNF-␣, although the kinetics of the prostratin-mediated response are slower.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We find that prostratin effectively activates the latent provirus in multiple independently derived J-Lat T-cell clones. These results are in agreement with recently published results demonstrating prostratin-mediated activation of latent virus in the SCID-HU Thy/Liv system and in the blood of patients with HAART-suppressed HIV (14,15). We observed that prostratin induces similar levels of proviral gene transcription as TNF-␣, although the kinetics of the prostratin-mediated response are slower.…”
Section: Discussionsupporting
confidence: 93%
“…Considerable interest has recently focused on prostratin as an in vivo agent to purge latent HIV proviruses (6,14,15). As a cellular model of HIV latency, we employed the J-Lat T cells, which contain a full-length latent HIV provirus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, prostratin elicits pleiotropic effects relevant to HIV treatment. It causes downregulation of CD4, CXCR4 and, in some cases, CCR5 and thereby protects CD4 + T cells from infection [61,62] . Further investigation revealed that prostratin induces PKC-mediated phosphorylation, and the degradation of IκB and enables the subsequent release and penetration of transcriptional factor NF-κB into the cell nucleus, where NF-κB binds to LTRs, leading to transcriptional initiation [63] .…”
Section: Histone Methyltransferase Inhibitors (Hmti)mentioning
confidence: 99%